PENGARUH KONDISI AUDIO LATAR BELAKANG TERHADAP PERFORMA MEMORI KERJA VERBAL MAHASISWA - Malfiqha Arum Sari; Mochamad Rizki Maulana; Gina Haerunisa; Siti Nurajijah; Mustika Sari Dewi; Rifqi Farisan Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine and compare the effectiveness of various background audio conditions on verbal working memory processing among university students. A true experimental design with a within-subject repeated measures layout was employed, involving a net sample size of 30 active undergraduate students from Universitas Indonesia Membangun (INABA) selected through a random sampling technique. All participants received three levels of background audio treatments administered in a counterbalanced rotation: Silence, Instrumental Music, and Vocal Music. Verbal working memory performance was objectively measured using the accuracy scores of a Digit Serial Recall Task ranging from 5 to 9 digits. Primary data were analyzed utilizing a One-Way Repeated Measures ANOVA with post-hoc Pairwise Comparisons adjusted by Bonferroni correction. The results showed a highly significant difference in verbal working memory performance across the three audio conditions, F(2, 58) = 7,423, p = 0,001, with a partial 2 = 0,204. Post-hoc analysis revealed that the Vocal Music session produced the most destructive reduction in sequential recall compared to the Instrumental Music and Silence sessions. This study concludes that the impairment of working memory is dominated by the simultaneous mechanisms of the Changing-State Hypothesis and the Irrelevant Speech Effect within the phonological loop component. The practical implications of this research highlight the critical importance of mitigating noise pollution and implementing absolute silence during verbal learning activities that demand high cognitive concentration.